2019
DOI: 10.17533/udea.rccp.v32n2a04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic polymorphism in Pit1, GH, GHR and KCN3 on milk yield and body weight of Khuzestan (Iran) water buffaloes

Abstract: Background: Genetic information is necessary to devise strategic plans aimed to improve the genetic merit of buffalos. Objective: To assess the effect of genetic polymorphisms in GH, Pit-1, GHR, GHRHR, and KCN3 genes on milk production and body weight of Khuzestan water buffaloes. Methods: Blood samples were collected from 60 buffaloes from the Khuzestan province, Iran. Using the PCR-RFLP technique, the amplified and digested fragments of GH/AluI, GHR/AluI, GHRHR/ HaeIII, Pit1/HinfI, and KCN3/HindIII were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…They found that the meat yield trait since birth weight is related with the GHR genotypes in Anatolian water buffalo breed. Comparably with Özşensoy and Kara (2019), Ahmadzadeh et al (2019) determined three genotypes in both the GH and GHR genes, and a statistically significant effect on body weight in Iranian water buffalo breeds. In Table 4, it can be observed the relationships between the GH-MspI and GH-AluI polymorphisms and some economic traits in cattle and water buffalo.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…They found that the meat yield trait since birth weight is related with the GHR genotypes in Anatolian water buffalo breed. Comparably with Özşensoy and Kara (2019), Ahmadzadeh et al (2019) determined three genotypes in both the GH and GHR genes, and a statistically significant effect on body weight in Iranian water buffalo breeds. In Table 4, it can be observed the relationships between the GH-MspI and GH-AluI polymorphisms and some economic traits in cattle and water buffalo.…”
Section: Discussionmentioning
confidence: 59%
“…Among the available genomic tools, the use of single-nucleotide polymorphism (SNP) markers is particularly effective for selecting traits measured in a single sex, such as milk yield and milk composition (Venturini et al, 2014). Several studies have examined buffaloes to identify SNP markers associated with milk components (Gil et al, 2013;Ahmadzadeh et al, 2019;Liu et al, 2018). One of the most important of this SNP marker is the growth hormone (GH) gene region.…”
Section: Introductionmentioning
confidence: 99%
“…All of these findings were statistically significant (P < 0.001), with the AG genotype being highest. In a study conducted on 60 Iranian water buffalo breeds, 3 genotypes were determined in both the GH and GHR genes, and a statistically significant effect on body weight was determined (Ahmadzadeh et al, 2019). The LL genotype of the GH gene was reported as a possibly species-related trait for water buffaloes (Mitra et al, 1995;Pal and Chatterjee, 2010;Jammeda and Vataliya, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Selection techniques at the DNA level and quantitative trait locus (QTL) can help to accelerate quantitative selections through the identification of major genes controlling the economic traits. Milk yield and its quality in dairy cattle are quantitative traits and controlled by many genes which are potentially influenced by the growth genes (Ahmadi et al, 2015;Ahmadzadeh et al, 2019;Bayram et al, 2017;Szatkowska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The growth genes providing GH, GHRH, and Pit1 genes influence biological functions of the livestock, such as growth, development, proliferation of udder cells, and lactogenesis (Ahmadi et al, 2015;Ahmadzadeh et al, 2019;Bayram et al, 2017;Kiyici et al, 2019;Sami et al, 2011;Szatkowska et al, 2009). Bovine Growth Hormone Releasing Hormone (bGHRH) gene consists of five exons and four introns and locates in the chromosome number 13 (BTA-13).…”
Section: Introductionmentioning
confidence: 99%